Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
5: \(\left(\dfrac{2}{3}x^2-\dfrac{1}{2}y\right)^3=\dfrac{8}{27}x^6-\dfrac{2}{3}x^4y+\dfrac{1}{2}x^2y^2-\dfrac{1}{8}y^3\)
9, = \(\left(x^2\right)^2-\left(\dfrac{2}{5}y\right)^2=x^4-\dfrac{4}{25}y^2\)
10, = \(\left(\dfrac{x}{2}\right)^2-y^2=\dfrac{x^2}{4}-y^2\)
Bài 2:
Ta có: \(3n^3+10n^2-5⋮3n+1\)
\(\Leftrightarrow3n^3+n^2+9n^2+3n-3n-1-4⋮3n+1\)
\(\Leftrightarrow3n+1\in\left\{1;-1;2;-2;4;-4\right\}\)
\(\Leftrightarrow3n\in\left\{0;-3;3\right\}\)
hay \(n\in\left\{0;-1;1\right\}\)
11)
\(\dfrac{2x}{x+2}\) \(\times\) \(\dfrac{x^{2^{ }}-4}{4}\) - \(\dfrac{x}{2}\)
= \(\dfrac{2x}{x+2}\) \(\times\) \(\dfrac{x^2-2^2}{4}\) - \(\dfrac{x}{2}\)
= \(\dfrac{2x}{x+2}\) \(\times\) \(\dfrac{\left(x-2\right)\left(x+2\right)}{4}\) - \(\dfrac{x}{2}\)
= \(\dfrac{x\left(x-3\right)}{2}\)